(3efXheI aj eVGejf GdCNHGQ GdhGQOI aj BOGH GdeWGYe hGdeTGQH hefGaYgGs - (3GdfLaj, , GdCYSe, eMeO Hf Ydj Hf MSjf Hf eMeO ` J (B1233 (3g`s ((3Ydj Hf eMeO QVG cGTa GdZWGAs)
(3ChdgG (B:s
(3GdMeO ddg (B.. (3bGd fXQJ aj cJGH GdCWYeI ef GdOQhS eG GbJVi Cf CfXeg (B** (3eeG Hg Qhi ef GdBOGH YfO MVhQ GdCcd hGdTQGH (B** (3ecJajG HPGc Ch GfXQ eG QhGg aj Pdc HYV GdYdeG (B...s
(3BNQgG (B:s
.. (3Ch CaVd Gdbhe QajY GdTGf ceG bO GSJMHg GdcGTGfj (B** (3jLeY eGA Gdcd WTJ hGMO dCLd LeY GdTed agh GdhQGOG(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\297s
(3GdPQjYI (B1 \ 2315s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs